Ageing and long‐term CD4 cell count trends in HIV‐positive patients with 5 years or more combination antiretroviral therapy experience. Issue 4 (4th October 2012) - Wright, ST; Petoumenos, K; Boyd, M; Carr, A; Downing, S; O'Connor, CC; Grotowski, M; Law, MG; ,
<x xml:space="preserve">Abstract</x> Objectives The aim of this study was to describe the long‐term changes in CD4 cell counts beyond 5 years of combination antiretroviral therapy (cART). If natural ageing leads to a long‐term decline in the immune system via low‐grade chronic immune activation/inflammation, then one might expect to see a greater or earlier decline in CD4 counts in older HIV‐positive patients with increasing duration of cART. Methods Retrospective and prospective data were examined from long‐term virologically stable HIV‐positive adults from the Australian HIV Observational Database. We estimated mean CD4 cell count changes following the completion of 5 years of cART using linear mixed models. Results A total of 37 916 CD4 measurements were observed for 892 patients over a combined total of 9753 patient‐years. Older patients (> 50 years old) at cART initiation had estimated mean (95% confidence interval) changes in CD4 counts by year‐5 CD4 count strata (< 500, 500–750 and > 750 cells/μL) of 14 (7 to 21), 3 (–5 to 11) and –6 (–17 to 4) cells/μL/year. Of the CD4 cell count rates of change estimated, none were indicative of long‐term declines in CD4 cell counts. Conclusions Our results suggest that duration of cART and increasing age do not result in decreasing mean changes in CD4 cell counts for long‐term virologically suppressed patients, indicating that the level of immune recovery achieved during the first 5 years of treatment is sustained through long‐term cART.